Problematics of the Learning Proces of Islamic Religious Education in Junior High Schools - Pradmi, Tomi; Izmi, Nelly; Fatimah, Fatimah (Ahlussunnah: Journal of Islamic Education, 2022)
This research aims to determine the planning, implementation, and evaluation carried out in Islamic Religious Education learning. This research uses a qualitative method with a descriptive approach, namely describing the conditions that occur in the field as they are. The data sources in this research are Islamic Religious Education teachers, students, and the principal of Palembayan 01 Junior High School. Data collection techniques were carried out by means of interviews, observation, and documentation. Meanwhile, the sampling technique is using snowball sampling. The analysis results show that; i) learning strategy planning is less than optimal, including planning in learning objectives, choosing teaching materials that focus on book material without looking for additional references, learning techniques that are less varied, only using lecture and question and answer techniques, poor class management, ii) implementing strategies Islamic Religious Education learning is not consistent in carrying out the steps in using strategies, only using direct, expository learning strategies which are according to one's own wishes, discussions focused only on activity, iii) forms of learning evaluation questions given in the form of tests and non-tests, questions that less interesting because there are no pictures or tables, relying on questions. The results of this research can be used as initial data for future researchers to study in different contexts and studies.